Incentives and innovation? R&D management in Germany's high-tech industries during the second industrial revolution - Carsten Burhop; Thorsten Lübbers (Max Planck Institute for Research on Collective Goods, 2008)
The allocation of intellectual property rights between firms and employed researchers causes a principal-agent problem between the two parties. We investigate the working contracts of inventors employed by German chemical, pharmaceutical, and electrical engineering firms at the turn of the 20th century and show that some firms were aware of the principal-agent problem and offered performance-related compensation schemes to their scientists. However, neither a higher total compensation nor a higher share of variable compensation in total compensation is correlated with a higher innovative output. Thus, incentives techniques were already used during the early history of industrial research laboratories, but their impact on innovative output was unsystematic.
Keywords: N83; O31; J33; 330; Compensation packages; incentives; innovation; economic history; Germany; pre-1913; Industrielle Forschung; Leistungsorientierte Vergütung; Wissenschaftler; Agency Theory; Innovation; Deutschland (bis 1945)